Mechanistic roles of substitutional Fe dopants on catalytic acetylene-sensing process of flame-made SnO2 nanoparticles - Jirasak Sukunta (2018)
© 2018 King Saud University In this work, flame-spray-made Fe-doped SnO2 nanoparticles were comprehensively investigated for acetylene (C2H2) detection and the roles of Fe dopants on sensing mechanisms were explored. The sensing material properties were evaluated by X-ray diffraction, electron microscopy, N2 adsorption-desorption analysis, X-ray absorption/photoemission spectroscopy and UV–visible spectroscopy. The structural characterizations confirmed that the nanoparticles had a tetragonal nanocrystalline SnO2 phase and Fe3+ dopant species formed a solid solution with SnO2 lattice. The sensors were measured towards 0.15–3 vol% C2H2 in dry air at various working temperatures (200–350 °C). Gas-sensing data demonstrated that the optimal Fe doping level of 0.1 wt% led to a substantially enhanced response of 748.7 toward 3 vol% C2H2 with a decent response time of 2.5 s at the optimal working temperature of 300 °C. Furthermore, the optimal SnO2 sensor demonstrated high C2H2 selectivity against C2H5OH, NO2, H2, NH3, CO2, NO, H2S, CH4, C2H4O, C2H4 and N2O. Additional detailed analyses suggested that Fe3+ species played catalytic roles for enhancing C2H2 dissociation and oxidation. Thus, the Fe-doped SnO2 sensors were highly promising for selective and sensitive detections of acetylene in industrial applications.